Superwettable antibacterial textiles for versatile oil/water separation. Issue 5 (19th March 2019) - Vaidulych, Mykhailo; Shelemin, Artem; Hanuš, Jan; Khalakhan, Ivan; Krakovsky, Ivan; Kočová, Pavlína; Mašková, Hana; Kratochvíl, Jiří; Pleskunov, Pavel; Štěrba, Jan; Kylián, Ondrej; Choukourov, Andrei; et al.
Abstract: A gas‐phase deposition process based on the combination of nanoparticles (NPs) and thin films is developed to obtain either superhydrophobic or superamphiphilic nanocomposite coatings on filtration membranes. Superhydrophobic membranes are produced on nonwoven viscose fabric and they demonstrate selective absorption of nonpolar organic solvents from oil/water mixtures. Superamphiphilic membranes are produced on carbon cloth and found suitable for smart separation of light oil or heavy oil from water, with the efficiency above 99.97%. Incorporation of Cu NPs endow both types of the membranes with antibacterial properties. A twofold reduction in the metabolic activity of Escherichia coli is achieved after 24 hr of the incubation, which proves this environmentally friendly approach to be perspective for the development of multifunctional porous substrates. Abstract : An original low‐temperature plasma‐based method is developed for the fabrication of the multifunctional nanocomposite coatings on porous membranes. Combination of thin films and particles of plasma polymer enables tuning the wettability of nanocomposites, whereas embedding Cu nanoparticles (NPs) endows them with bactericidal properties. As a result, superhydrophobic and smart superamphiphilic membranes are obtained and utilized for the oil/water separation.